Effect of normobaric hypoxic exercise on blood pressure in old individuals - Hein, Markus; Chobanyan-Jürgens, Kristine; Tegtbur, Uwe; Engeli, Stefan; Jordan, Jens; Haufe, Sven (European journal of applied physiology, 2021)
To test the hypothesis that the combination of endurance training and hypoxia leads to greater improvements in resting and exercise blood pressure in old sedentary individuals compared to endurance training only.
Published online: 23 December 2020
Gesehen am 20.11.2023